Financial Inclusion Measures of the Indian Government - Dr. S. Ramesh (HM Journals, 2022)
This comprehensive study explores the multifaceted landscape of financial inclusion measures undertaken by the Indian government. By examining initiatives such as the Pradhan Mantri Jan Dhan Yojana (PMJDY), Direct Benefit Transfer (DBT), digital payment systems, small finance banks, payment banks, and financial literacy campaigns, the study delves into the objectives, implementation strategies, achievements, and challenges of these measures. The analysis highlights the transformative impact of financial inclusion on marginalized populations, while also addressing persisting challenges such as low financial literacy and inadequate infrastructure. The study underscores the necessity of collaborative efforts among government bodies, financial institutions, technology enablers, and civil society organizations to ensure a holistic and sustainable approach to financial inclusion.